PHYSICAL APPLICATION OF THE SPHERICAL SOLUTION OF THE RICCI FLOW EQUATION IN FOUR DIMENSIONAL SPACETIME - SUROSO (NIM. 20208007), AGUS
The Ricci flow (RF) is a flow equation which describe a diffusive process acting on the Riemannian metric driven by its Ricci curvature. This equation was introduced by Richard Hamilton in 1982 as a tool for proving the Thurston's geometrization conjecture for closed 3-manifolds. The equation can be applied in general relativity. Solution of the RF equation is a Schwarzschild-de Sitter which evolves linearly in non-coordinate parameter T (tau). We study some physical application of the solution concerning light bending, perihelion precession, and surface gravity of black hole.